Exact and Easy: Decimalization in Early Modern England. - Crowley, John E. (Journal of Interdisciplinary History)
Thanks to the metrological hegemony of the metric system, decimalization is now synonymous with quantitative precision, efficient calculation, and objective understandability. But a historicization of decimalization with respect to measurements reminds us that such objectivity cannot be taken for granted. Using decimal fractions explicitly required that people set aside traditional measurements for money, land, commodities, and time. Two centuries before the development of the metric system, the application of decimalization explicitly encouraged anticustomary approaches to measurement. Drawing interdisciplinarily on mathematical history, metrological history, and quantitative epistemology, with Stuart England as a case study, this article shows that quantitatively minded people rapidly adopted decimal fractions for measurements because they had explicitly advantageous exactness and ease of calculation.